Hole mobility modulation in single‐crystal metal phthalocyanines by changing the metal–π/π–π interactions - Jiang, Hui (2020)
Weak intermolecular interactions in organic semiconducting molecular crystals play an important role in determining molecular packing and electronic properties. Single crystals of metal‐free and metal phthalocyanines were synthesized to investigate how the coordination of the central metal atom affects their molecular packing and resultant electronic properties. Single‐crystal field‐effect transistors were made and showed a hole mobility order of ZnPc>MnPc>FePc>CoPc>CuPc>H2Pc>NiPc. Density functional theory (DFT) and 1D polaron transport theory reach a good agreement in reproducing the experimentally measured trend for hole mobility. Additional detail analysis at the DFT level suggests the metal atom coordination into H2Pc planes can tune the hole mobility via adjusting the intermolecular distances along the shortest axis with closest parallel π stackings.